Svetovni literarni sistem - Juvan, Marko (Primerjalna književnost, 2009)
The original Goethean (cosmopolitan, but peripheral) notion of world literature as analogous to the capitalist world-system has become relevant to the transnational comparative studies: it implies conceptual-evaluative background, practices, media, and institutions that allow intercultural transfer, intertextual absorption of global cultural repertoires, and self-conscious production for international audiences. Since the 19th-century cultural nationalism, the theoretical or poetic consciousness of world literature, its intertextual coherence, and its material networks have been "glocalized." The literary world system is accessible through the archives of localized cultural memory and particular cognitive or linguistic perspectives, whereas centrality and peripherality are variables that depend on the historical dynamics and system evolution.
Keywords: primerjalna literarna veda; svetovna književnost; literarni sistem; globalizacija; globalization; kozmopolitizem; kulturni transfer